KHUSNUDZON DAN PSYCHOLOGICAL WELL BEING PADA ORANG DENGAN HIV/AIDS - Qurotul Uyun; Irman Nuryadin Siddik (Psikis : Jurnal Psikologi Islami, 2017)
The aims of this research is determine the relation between khusnudzon and psychological well being in people living with HIV / AIDS. The hypothesis in this research is there is positive relation between khusnudzon psychological well being in people living with HIV / AIDS. To test the hypothesis of the research, researchers collecting data using a scale of psychological well being adapted from a Ryff’s scale (1989) and adapted khusnudzon scale of Dewi’s scale (2015) is based on the theory from Rusydi (2012). The scale distributed to 55 people living with HIV/ AIDS who are the members of the VP foundation. Correlation analysis show the coefficient of r = 0.543 with significance (p) <0,01 so that hypothesis is accepted.